2012
DOI: 10.1016/s0140-6736(12)61022-8
|View full text |Cite
|
Sign up to set email alerts
|

A call to action for comprehensive HIV services for men who have sex with men

Abstract: Where surveillance has been done, it has shown that men (MSM) who have sex with men bear a disproportionate burden of HIV. Yet they continue to be excluded, sometimes systematically, from HIV services because of stigma, discrimination, and criminalisation. This situation must change if global control of the HIV epidemic is to be achieved. On both public health and human rights grounds, expansion of HIV prevention, treatment, and care to MSM is an urgent imperative. Effective combination prevention and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
178
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(180 citation statements)
references
References 32 publications
0
178
1
1
Order By: Relevance
“…A factor related to the sexual practices of MSM and which was associated with HIV infection and other STI is the high number of partners, which can increase their exposure to HIV infection, especially with inconsistent condom use in receptive anal sex, which can occur due to alcohol use, psychoactive substances before and during sex, or as a result of stigma and discrimination 37,38 . Some RDS studies have found fewer sexual partners than in this study 24,28,39,40 , but our findings are close to other results of RDS studies with MSM 6,25,27,30 .…”
Section: Discussionmentioning
confidence: 99%
“…A factor related to the sexual practices of MSM and which was associated with HIV infection and other STI is the high number of partners, which can increase their exposure to HIV infection, especially with inconsistent condom use in receptive anal sex, which can occur due to alcohol use, psychoactive substances before and during sex, or as a result of stigma and discrimination 37,38 . Some RDS studies have found fewer sexual partners than in this study 24,28,39,40 , but our findings are close to other results of RDS studies with MSM 6,25,27,30 .…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] In Romania, negative attitudes toward gender and sexual minorities are among the highest in Europe, 9,10 leading many LGBT individuals to conceal their identities from healthcare providers and avoid seeking healthcare, which is widely recognized as being unresponsive to LGBT health concerns. [10][11][12] Stigma-related barriers to healthcare exacerbate sexual orientation-based health disparities, including increasing HIV and sexually transmitted infection (STI) incidence.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Stigma-related barriers to healthcare exacerbate sexual orientation-based health disparities, including increasing HIV and sexually transmitted infection (STI) incidence. [4][5][6][7]10,13 Two international sexual health surveys indicate that HIV prevalence among Romanian men who have sex with men (MSM) was 5% in 2008 14 and 18% in 2014, 15 suggesting a potential recent increase in HIV infection. Romanian LGBT individuals report some of the highest rates of health services dissatisfaction, barriers to healthcare, and mental health problems (e.g., depression, anxiety, and suicidality), yet indicate the highest desire to use LGBT-affirmative healthcare, among their European peers.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, while research advances have suggested that to achieve an AIDS-free generation, inclusion of MSM in HIV research interventions is imperative, the unmet health needs of MSM in this region are currently being heightened by discriminatory laws prohibiting these men from attaining a rights-defined health status [3,48]. Also, despite evidence suggesting that great strides have been made in HIV prevention among behaviorally heterosexual populations, the rates of HIV continue to increase disproportionately among MSM [55].…”
Section: Hiv Disparities and Syndemic Conditions Among Msm In Ssa: Pamentioning
confidence: 99%